2004
DOI: 10.3177/jnsv.50.351
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Capsinoid on Serum and Liver Lipids in Hyperlipidemic Rats

Abstract: SummaryWe compared the effects of capsinoid, a non-pungent component, on serum and liver lipids, with that of synthetic capsaicin in hyperlipidemic rats. Male Wistar rats of 9 wk old were divided into 4 groups: a control group receiving a high-fat diet containing 1% cholesterol, and capsaicin, capsinoid-I and capsinoid-II groups supplemented with 0.1mmol of N pelargonylvanillylamide (synthetic capsaicin), and 0.1mmol and 1.0mmol of capsinoid (capsiate: dihydrocapsiate= 63:37) per kg of control diet, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…Treatment of hyperlipidemic rats with capsaicin reduces levels of serum-and hepatic lipids, accompanied by high-and low activity of hepatic TG lipase and fatty acid synthetase, respectively. 33) In our study, these compounds did not block LD formation. A possible interpretation of this inconsistency is that the potency of OA to induce LDs is so high that the inhibitory effects of the compounds are overwhelmed.…”
Section: Discussionmentioning
confidence: 70%
“…Treatment of hyperlipidemic rats with capsaicin reduces levels of serum-and hepatic lipids, accompanied by high-and low activity of hepatic TG lipase and fatty acid synthetase, respectively. 33) In our study, these compounds did not block LD formation. A possible interpretation of this inconsistency is that the potency of OA to induce LDs is so high that the inhibitory effects of the compounds are overwhelmed.…”
Section: Discussionmentioning
confidence: 70%
“…High-fat diets containing capsaicin lower adipose tissue weight (Kawada et al, 1986a), reduce low-density lipoprotein (LDL) cholesterol and increase highdensity lipoprotein (HDL), cholesterol and triglycerides (Kawada et al, 1986a;Srinivasan and Chandrasekhara 1992;Saito et al, 1999;Lee et al, 2003;Tani et al, 2004). Small amounts of capsaicin, when used topically, induce vasodilatation, but at higher concentrations cause vasoconstriction .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that exercise suppresses liver lipid accumulation (26), possibly via mechanisms involving increased fat oxidation and decreased lipogenesis in the liver (7,42). Furthermore, capsiate was reported to reduce hepatic TG levels in rats fed a HFD (53), and CSNs were shown to reduce hepatic TG levels in mice fed a HFD (Inoue N, Nogusa Y, Hara-Kimura Y, OkabeNogusa Y, Ohyama K, Tsukamoto-Yasui M, and Ono K, unpublished observations). These data suggested that the combination of exercise and CSNs may suppress lipid accumulation by increasing fat oxidation in the liver.…”
Section: Discussionmentioning
confidence: 99%